Letters to Florence O'Donoghue from various individuals (M - N) in response to queries and newspaper advertisements seeking information on Liam Lynch - O'Donoghue, Florence, 1895-1967 (1952)
Correspondents are Henry F. Meagher, Kathy B. Moloney , Wm. Mullins, Sr. Teresita Mullins, D. Mulvihill, Denis Murray, Padraigín Ní Aodhagáin and Caitlín Ní Buachalla. Includes some poetry by Henry F. Meagher on the subject of Liam Lynch.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Irish Republican Army; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-